Revealed Social Preferences for Equality and Growth - Kiefer, David; Khan, Shahrukh Rafi (Journal of Income Distribution®, 2008)
Using the Kuznets inverted-U-shaped association as a structuralconstraint, we model the social tradeoff between changing inequalityand changing income. If observed outcomes for recent decadesare taken as constrained political-economic optima, this model identifiesthe parameters of a social welfare function. Our cross-countryregression results tentatively suggest that the world is becoming ananti-egalitarian place.